2015
DOI: 10.4067/s0301-732x2015000100018
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Yucca schidigera liquid extract on water quality and survival of Pacific Red Snapper Lutjanus peru during acclimatization

Abstract: RESUMENEl objetivo de este estudio fue determinar el efecto del extracto líquido de Y. schidigera sobre la calidad del agua y prevención de la mortalidad del pargo rojo del Pacífico L. Peru, durante la transferencia del medio silvestre a condiciones del laboratorio. Se utilizaron tres tratamientos: extracto líquido concentrado 100% de Y. schidigera natural fue administrado en baja concentración (0,25 mg L -1 ) y alta concentración (0,75 mg L -1 ), además de un grupo control sin extracto. El extracto líquido fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Santacruz-Reyes and Chien demonstrated a decrease in the TAN level with the addition of Y. shidigera extract in the aquaria of Nile tilapia (O. niloticus [21]) and juvenile Kuruma shrimp (Marsupenaeus japonicas [1]). Vargasmachuca et al demonstrated similar effects with Y. schidigera extract added to the water of Pacific Red Snapper (Lutjanus peru) during acclimatization [22]. In some cases, however, such use resulted in the death of all animals after a few hours [1].…”
Section: Discussionmentioning
confidence: 90%
“…Santacruz-Reyes and Chien demonstrated a decrease in the TAN level with the addition of Y. shidigera extract in the aquaria of Nile tilapia (O. niloticus [21]) and juvenile Kuruma shrimp (Marsupenaeus japonicas [1]). Vargasmachuca et al demonstrated similar effects with Y. schidigera extract added to the water of Pacific Red Snapper (Lutjanus peru) during acclimatization [22]. In some cases, however, such use resulted in the death of all animals after a few hours [1].…”
Section: Discussionmentioning
confidence: 90%
“…Recently, saponins extracted from plants such as yucca and quillaja have been gaining attention due to their benefits as antiprotozoal, growth promoter, and ammonia binding agents in aquaculture and livestock production systems (Adegbeye et al, 2019; Castillo‐Vargasmachuca et al, 2015; Chepete, Xin, Mendes, Li, & Bailey, 2012; Hassan, Yusuf, Badran, Griesh, & Zidan, 2017; Matusiak et al, 2016). In the case of Pacific white shrimp, the biological function of yucca extracts was to enhance the rearing water quality, the shrimp growth performance, and the nonspecific immunity, with promising results (Hernández‐Acosta et al, 2016; Santacruz‐Reyes & Chien, 2012; Yang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of studies on the application of saponins in aquaculture have focused on their use as natural growth promoters when included in feeds for fish and shrimp (Francis, Makkar, & Becker, 2002; Kelly & Kohler, 2003; Paray, Hoseini, Hoseinifar, & Van Doan, 2020; Serrano, Focken, Francis, Makkar, & Becker, 2000; Yang, Tan, Dong, Chi, & Liu, 2015). Only a few authors have assessed their potential benefits when applied directly in the tanks or ponds, in order to reduce the concentration of ammonia within the culture environment (Castillo‐Vargasmachuca et al, 2015; Fayed et al, 2019; Khalil, Saad, Ragab, & Mohammed, 2015; Santacruz‐Reyes & Chien, 2010, 2012). Oak ( Quercus robur ) is known to have a high content of bioactive compounds (Burlacu, Nisca, & Tanase, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results correspond with Güroy et al (2016) who found a significant reduction in TAN excretion with 0.3% dietary inclusion of YS and QS extract to the juvenile striped catfish diet, compared to the control. In this context, many studies have focused on the role of YS in mitigating ammonia in aquaculture water with promising findings (Castillo Vargasmachuca et al, 2015;Hassan et al, 2017;Yang et al, 2015;Yu et al, 2015). In this regard, YS inclusion can lower TAN and UIA in the carp fish (Dawood et al, 2021;Wang et al, 2020), Nile tilapia (Abdel-Tawwab et al, 2021;Engler et al, 2018), catfish (Güroy et al, 2014;Kelly & Kohler, 2003) and Pacific white shrimp (Litopenaeus vannamei) and Kuruma shrimp (Marsupenaeus japonicus) (Santacruz-…”
Section: Discussionmentioning
confidence: 99%